Synthesis of N-functionalized 2,3-disubstituted benzofurans/naphthofurans from para-quinone methides and isocyanides via the [4+1] annulation pathway - Kale, Someshwar B.; Kumar, Manish; Shinde, Dinesh R.; Krishna, Gamidi Rama; Das, Utpal (Organic Chemistry Frontiers, 2023)
A scandium triflate catalyzed [4 + 1] cycloaddition reaction of 2-hydroxy-substituted para-quinone methides and isocyanides has been developed. This operationally simple, efficient and practical protocol provides straightforward access to a variety of N-functionalized 2,3-disubstituted benzofuran/naphthofuran derivatives with broad functional group compatibility and good scalability.